The effectiveness of RIPAT approach in influencing smallholder farmers’ agroecological transition in Ruangwa District, Tanzania - Nickson J. Ringo; John F. Kessy; Emmanuel T. Malisa (Discover Agriculture)
Abstract Agroecology approach is viewed as an alternative paradigm that promotes sustainable production and environmental conservation. Extension services are crucial for diffusing agroecological knowledge, facilitating the adoption of agroecological techniques. The Rural Initiatives for Participatory Agricultural Transformation (RIPAT) is a participatory extension approach developed to bridge the agricultural technology gap by disseminating sustainable agricultural innovations. This study aimed to assess the extent of agroecological transition among smallholder farmers and explore the role of RIPAT approach, alongside other factors, in this transition in Ruangwa District. Data were collected from 252 randomly selected farmers using questionnaire surveys and focus group discussion, and analyzed using descriptive and inferential statistics. Results indicated that all non-RIPAT farmers (100%) were in level 1; non-agroecological. In contrast, nearly half (47.6%) of RIPAT farmers showed progress in the agroecological transition: 37.3% were at level 2 (incipient transition to agroecology), 9.5% at level 3 (system in transition to agroecology), and 0.8% at level 4 (advanced agroecological system). This progress is primarily due to the agroecology-related training they received, which enhanced their knowledge and improved their practices. RIPAT farmers achieved higher average scores (over 50%) in the agroecology elements of Recycling, Efficiency, Co-Creation and Sharing of Knowledge, and Human and Social Values. However, for elements like Synergies, Resilience, and Responsible Governance, farmers were still lagging. The study further indicated that exposure to the RIPAT approach, access to information, and farm size were statistically significant factors influencing farmers’ agroecological transition. Enhancing animal husbandry practices and promoting agroforestry techniques are recommended to foster farm synergy and resilience through integrated farming systems. Additionally, establishing producer associations could strengthen responsible governance by improving farmers' collective bargaining power. The study recommends adoption of participatory extension approaches, such as the RIPAT approach, for transferring agroecological knowledge to promote farmers’ agroecological transition.